Technology Integration in Teaching Materials for Optimizing Students’ Learning Skills Through PJBL Approach - Paramitha, Adelia Ayu; Nurwahidin, Muhammad; Rusminto, Nurlaksana Eko; Firdaus, Rangga (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research examines the integration of technology in teaching materials to improve students’ learning skills through the Project-Based Learning (PJBL) approach. Technology is used as a medium for collaboration, reflection and data collection that supports learning experiences that are interactive, engaging and relevant to students’ real lives. The application of the Technological Pedagogical Content Knowledge (TPACK) framework helps teachers design effective and engaging learning experiences. The results show that the use of digital platforms such as Google Classroom, Edmodo and Microsoft Teams can improve students’ motivation, engagement and 21st century skills, including collaboration, critical thinking and creativity. In addition, the integration of technology allows students to learn flexibly and actively participate in real projects, which ultimately supports the optimal success of implementing PPA